Ayurvedic Management of Ovarian Cyst: A Case Report - Varun Gupta; Dnyanesh Joshi; Bhushan Mhaiskar; Utkarsha Khaire (Journal of Clinical and Diagnostic Research)
Ovarian cysts are fluid-filled sacs that develop either on or within a woman’s ovaries, which are part of the female reproductive system. They are frequently encountered and can form at any stage of life, but they are most often detected in women during their reproductive years. According to Ayurveda, ovarian cysts can be correlated to Kaphaja Granthi Roga. A 49-year-old female patient came to the Outpatient Department (OPD), with complaints of pain in the pelvic region, bloating, heaviness in the lower abdomen, and changes in menstrual patterns in the last six months. Her ultrasonography report suggested an ovarian cyst measuring 66.2×44.2 mm. The condition was addressed with a combination of various traditional ayurvedic medicines like Kanchnar guggulu 2 tab twice a day, Chandraprabha vati 2 tab twice a day, Bruhat panchmula kwath 20 mL twice a day, Ajmodadi churna 1 tsf at night, Varunadi kashyam 10 mL twice a day, all medicine were given for six months. The patient was satisfied with the outcomes. According to her Ultrasound (USG) reports, after six months of treatment there was no evidence of an ovarian cyst, and her symptoms also demonstrated improvement. The current case underscores the effectiveness of Ayurvedic treatment in achieving positive outcomes for managing ovarian cysts.